2000
DOI: 10.1093/oxfordjournals.jbchem.a022730
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Cell Growth Is Regulated by Purine Biosynthesis via ATP Production and G1 to S Phase Transition

Abstract: We recently showed that an increased supply of purine nucleotides increased the growth rate of cultured fibroblasts. To understand the mechanism of the growth rate regulation, CHO K1 (a wild type of Chinese hamster ovary fibroblast cell line) and CHO ade (-)A (a cell line deficient in amidophosphoribosyltransferase, a rate-limiting enzyme of the de novo pathway) were cultured under various conditions. Moreover, a defective de novo pathway in CHO ade (-)A cells was exogenously restored by 5-amino-4-imidazole-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 0 publications
3
56
0
Order By: Relevance
“…Previous findings have demonstrated that de novo purine biosynthesis is closely related to the cell cycle (19,20,25,(30)(31)(32)(33). Studies of other enzyme complexes have suggested that the assembly or disassembly of an enzyme cluster may be correlated with cellular events, such as developmental cues or metabolic states of the cell (33); for example, the replitase, a six-enzyme complex involved in DNA replication, has been shown to exist only during S phase (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings have demonstrated that de novo purine biosynthesis is closely related to the cell cycle (19,20,25,(30)(31)(32)(33). Studies of other enzyme complexes have suggested that the assembly or disassembly of an enzyme cluster may be correlated with cellular events, such as developmental cues or metabolic states of the cell (33); for example, the replitase, a six-enzyme complex involved in DNA replication, has been shown to exist only during S phase (34).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this protein assembly and its putative function(s) clearly suggest that the spatial organization of pathway enzymes into purinosomes within a cell play an important role in meeting the cellular demand for purines (18). Although many studies have implied up-regulation of the de novo purine biosynthetic pathway during cell cycle progression (14,(19)(20)(21), here we used time-lapse microscopy to determine whether a correlation exists between the cell cycle stage and the number of cells with purinosomes or the cells' purinosome content. Two different cell types, HeLa and LND cells, were used, with the latter deficient in purine salvage, to assess the effect of increased demand on the de novo pathway for purine biosynthesis and the attendant consequences for purinosome assembly.…”
mentioning
confidence: 99%
“…Decreased AdoMet synthesis alters methylation patterns in CpG islands in DNA and can result in histone hypomethylation, which can alter gene expression (2). Proliferating cells also require the de novo synthesis of purines to maintain rates of DNA synthesis (14).…”
mentioning
confidence: 99%
“…This tetramer may be a complex of mhATase subunits and hamster ATase subunits inactivated by a mutation in CHO ade ÏȘ A cells because hamster ATase was always found in the form of tetramers, even in the presence of PRPP, and because the less common tetrameric forms of hATase and mhATase were detected along with the major dimeric forms in the presence of PRPP (data not shown). 2 Mutual Regulation of de Novo and Salvage Pathways-Purine nucleotides are synthesized preferentially by the salvage pathway as long as hypoxanthine is available, with concomitant inhibition of the de novo pathway for sparing the energy expenditure required for de novo synthesis (1,11). In ÏȘ A Ï© mhATase cells, the suppression of the de novo pathway by the salvage pathway was strongly inhibited even in the presence of 2 T. Yamaoka and M. Itakura, unpublished data.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that purine de novo synthesis is a determinant of intracellular ATP concentration and promotes G 1 to S phase transition in the cell cycle, i.e. the initiation of DNA synthesis (11). Therefore, ATase and its feedback inhibition probably regulate DNA and protein syntheses through ATP production.…”
Section: Contributions Of Atase and Its Feedback Regulation To Varioumentioning
confidence: 99%